Sosialisasi Pembuatan Spray Anti Nyamuk dari Tanaman Serai Wangi dari Tanaman Serai Wangi dalam Pencegahan Penyakit Demam Berdarah di Kampung Long Iram Seberang - Andriana, Nita; Putra, Dhimaz Pratama; Belawing, Huriansyah; Nissa, Indah Khoirun; Al Rasyid, Muhammad Fauzan; Janhariyanti; Cahyani, Annisa Dwi; Ngau, Florentinus Raynaldi; Hersoyo, M Charis Ario; Lestari, Ida Ayu Indira Dwika (Jurnal Abdita Naturafarm, 2024)
The Aedes aegypti mosquito is a species of mosquito that is known to be the main factor in the spread of Dengue Hemorrhagic Fever (DHF). This outreach aims to educate about the potential of the citronella plant as a natural mosquito repellent. Citronella (Cymbopogon nardus L.) is a plant that contains essential oils consisting of citronellal (27.87%), citronellol (11.85%), geraniol (22.77%), geranial (14.54%) , neral (11.21%). The citronellol compound contained in citronella essential oil has toxic properties that cause dehydration in animals, especially insects. In the Flagship KKN program Batch 50, KUBAR 12 Group, Mulawarman University innovated in making anti-mosquito spray from citronella plants and provided outreach and carried out direct practice with PKK women in Long Iram Seberang Village, numbering approximately 20 people.  The manufacturing process includes drying, cutting, boiling, and mixing with alcohol to maximize the effectiveness of mosquito repellent. The results of this activity show that the resulting spray can last for approximately three days at room temperature and up to seven days if stored in the refrigerator, making it a simple but effective solution in protecting families from mosquito bites. It is hoped that this activity will succeed in increasing public awareness of the importance of maintaining environmental cleanliness and identifying local habits that can naturally reduce the risk of spreading dengue fever